EFFECT OF PRODUCT INNOVATION ON PERFORMANCE OF PRINTING SMES IN KAMPALA CENTRAL DISTRICT - Nakato, Moureen; Ngigi, Bilha; Andemariam, Kifleyesus (European Journal of Business and Strategic Management, 2021)
Purpose: The purpose of this study was to establish the effect of product innovation on performance of printing SMEs in Kampala Central District Methodology: The study used the explanatory design. The study conducted a census on a target population of 125printing SMEs operating in Kampala Central district. Data were collected using semi-structured questionnaires that were self- administered to managers of printing SMEs. Data analysis was conducted using SPSS software program v 25.0 where both descriptive and inferential statistical analyses were done. In particular, frequencies, percentages, mean scores, standard deviation and correlation analyses were used and the resultant presentation was done using figures and tables. Results: The study established that product innovation positively affected performance of printing SMEs. The study also revealed that use of graphic designs, digital printing and polymer sheets were among the major product innovations that were used which was represented by mean scores of 4.17, 3.95 and 3.81 respectively. Unique contribution to theory, practice and policy: The study recommends that printing firms should constantly endeavor to invest in different new product designs and improve on the existing products so as to attain a competitive advantage against competitors. For example, holographic and scratch off foils are some of the new products that firms can take advantage of. Holographic foil adds a thrilling effect that provides a high-tech look while scratch-off foil covers things that can be revealed by just a scratch creating an interactive print. Such products can bring more traffic and sales to the business as they are attractive and are perceived to have higher value. Additionally, the new products should be designed in a way that meets customer needs in the dynamic market environment.